Does osteoporosis influence the marginal peri‐implant bone level in female patients? A cross‐sectional study in a matched collective. (8th May 2017) - Wagner, Florian; Schuder, Krisztian; Hof, Markus; Heuberer, Simone; Seemann, Rudolf; Dvorak, Gabriella
Abstract: Background/purpose: Osteoporosis, being a homeostatic imbalance, affects the remodeling of bone. Whether this catabolic bone disease influences peri‐implant marginal bone remodeling remains unknown so far. The purpose of this study was to evaluate the influence of osteoporosis on peri‐implant marginal bone loss (MBL) in postmenopausal women. Materials and methods: In a matched collective, radiographic peri‐implant bone level (at baseline and at follow‐up examinations) was compared in healthy and osteoporotic women. General health and behavioral history of the patients were recorded using a printed questionnaire. Results: A best fit matching procedure generated a sample of 48 women with a total of 204 implants matched at patient and implant level that was further statistically analyzed. The mean mesial MBL—statistically corrected to report the first year—was −0.6 ± 1.2 mm (range: −5.1 to 2.2) in the healthy control group and −1.1 ± 1.3 mm (range: −5.3 to 2.2) in the osteoporotic group. Similarly, the mean distal MBL was −0.5 ± 1.3 mm (range: −5.1 to 4.8) in the healthy control group and −1.2 ± 1.3 mm (range: −4.7 to 1.6) in the osteoporotic group, respectively. The base linear regression models including solely osteoporosis and time without any other confounders revealed a significant influence of osteoporosis and time since implant placement on the MBL at the mesial and the distal implant aspect. The significance of osteoporosis on bone loss did not change incorporating the confounders: bone level at implantation, smoking, jaw, location, surface, concrement, plaque, augmentation, edentulism in opposing and implant jaw, bisphosphonates, vitamin D, fixed versus removable prosthetics, connection type. Conclusions: There is no contraindication to place dental implants in osteoporotic patients. This study implicates to respect the bone level at implant placement and not to place the implant below bone level if possible.